1996
DOI: 10.1111/j.2042-7174.1996.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing community pharmacy services wanted by local people: information and advice about prescription medicines

Abstract: An extended information service on prescription medicines was evaluated in four community pharmacies over a period of 11 months, including a three-month pilot phase. Written patient information leaflets (PILs) and structured verbal advice designed according to the preferences of local people were provided by the pharmacist to patients prescribed any of three study drugs -amoxycillin, atenolol or ibuprofen. A total of 1,614 PILs were issued. Data were collected from a sample of 3 11 recipients about their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Written information combined with verbal counselling has been shown to increase drug knowledge recall (Morris & Halperin, 1979;Peura, Klaukka, Hannula, & Eerikainen, 1993;Livingstone et al, 1996) as well as increase compliance to therapy (Gotsch & Liguori, 1982;Myers & Calvert, 1984;Blaikie, 1999;Machuca, Espejo, Gutierrez, Machuca, & Herrera, 2003;AlSaffar, Deshmukh, Carter, & Adib, 2005). Using written drug information while counselling patients, also enhances the professional role of pharmacists, provides an opportunity for practising clinical pharmacy and allows pharmacists to fulfil their professional role in providing information to, and becoming more involved with the consumer (Dolinsky & Sogol, 1989).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Written information combined with verbal counselling has been shown to increase drug knowledge recall (Morris & Halperin, 1979;Peura, Klaukka, Hannula, & Eerikainen, 1993;Livingstone et al, 1996) as well as increase compliance to therapy (Gotsch & Liguori, 1982;Myers & Calvert, 1984;Blaikie, 1999;Machuca, Espejo, Gutierrez, Machuca, & Herrera, 2003;AlSaffar, Deshmukh, Carter, & Adib, 2005). Using written drug information while counselling patients, also enhances the professional role of pharmacists, provides an opportunity for practising clinical pharmacy and allows pharmacists to fulfil their professional role in providing information to, and becoming more involved with the consumer (Dolinsky & Sogol, 1989).…”
Section: Introductionmentioning
confidence: 95%
“…There are many factors that influence readership, in particular the nature of the interaction with the healthcare professional when the information is provided to the patient (Koo et al, 2002(Koo et al, , 2003. Patients view written information as less helpful than face-to-face counselling (Raynor et al, 2004) and prefer to receive written information and verbal counselling from pharmacists (Culbertson, Arthur, Rhodes & Rhodes 1988;Livingstone, Pugh, Winn, & Williamson, 1996;Sleath & Wurst, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Pharmacists have expressed a preference for using both modes of information provision (Kimberlin & Berardo, 1987;Schommer & Wiederholt, 1994). The combination has been shown to increase drug knowledge recall (Morris & Halperin, 1979;Peura, Klaukka, Hannula & Eerikainen, 1993;Livingstone et al, 1996) and improve compliance (Gotsch & Liguori, 1982;Myers & Calvert, 1984;Machuca, Espejo, Gutierrez, Machuca & Herrera, 2003;Al-Saffar, Desmukh, Carter & Adib, 2005), over either intervention alone.…”
Section: Introductionmentioning
confidence: 94%
“…Research has shown that consumers favour receiving written information (Lam & Krass, 1995;Livingstone, Pugh, Winn & Williamson, 1996;Sleath & Wurst, 2002) and consider an information leaflet about medicines useful (Mottram & Reed, 1997;Koo, Krass & Aslani, 2002). While some patients prefer to receive drug information from their physician (Hargie, Morrow & Woodman, 1992), others expect to receive both written and verbal medication information from pharmacists (Culbertson, Arthur, Rhodes & Rhodes, 1988;Livingstone et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…Studies which have measured counselling rates from the consumers' perspective have shown rates ranging from 8% to 56% [18][19][20][21]. Therefore, an average counselling rate of 30% was estimated.…”
Section: Research Design and Sample Sizementioning
confidence: 99%